The N termini of a-subunit isoforms are involved in signaling between vacuolar H+-ATPase (V-ATPase) and cytohesin-2 - Dip, Phat Vinh (2013)
Previously, we reported an acidification-dependent interaction of the endosomal vacuolar H+-ATPase (V-ATPase) with cytohesin-2, a GDP/GTP exchange factor (GEF), suggesting that it functions as a pH-sensing receptor. Here, we have studied the molecular mechanism of signaling between the V-ATPase, cytohesin-2, and Arf GTP-binding proteins. We found that part of the N-terminal cytosolic tail of the V-ATPase a2-subunit (a2N), corresponding to its first 17 amino acids (a2N(1–17)), potently modulates the enzymatic GDP/GTP exchange activity of cytohesin-2. Moreover, this peptide strongly inhibits GEF activity via direct interaction with the Sec7 domain of cytohesin-2. The structure of a2N(1–17) and its amino acids Phe5, Met10, and Gln14 involved in interaction with Sec7 domain were determined by NMR spectroscopy analysis. In silico docking experiments revealed that part of the V-ATPase formed by its a2N(1–17) epitope competes with the switch 2 region of Arf1 and Arf6 for binding to the Sec7 domain of cytohesin-2. The amino acid sequence alignment and GEF activity studies also uncovered the conserved character of signaling between all four (a1–a4) a-subunit isoforms of mammalian V-ATPase and cytohesin-2. Moreover, the conserved character of this phenomenon was also confirmed in experiments showing binding of mammalian cytohesin-2 to the intact yeast V-ATPase holo-complex. Thus, here we have uncovered an evolutionarily conserved function of the V-ATPase as a novel cytohesin-signaling receptor.